Histološke spremembe dojke med mesečnim ciklusom in v različnih starostnih obdobjih ženske - Cör, Andrej (Medicinski razgledi, 1999)
In the breast biopsy analysis we are frequently encounter with normal histological pictures of the breast tissue. Breast tissue has wide spectrum of"normal histology" in relation to phase of menstrual cycle and the age of woman. For the purpose to help students to study breast histology and embryology, the author described the embryology of mammary gland as well as histological picture of the breast. He emphasised the changes that occur in breast tissue in relation to the phase of menstrual cycle and the age of woman.
Keywords: Breast; dojke; Embryology; histologija; Anatomy and histology; mlečne žleze; Menstrual cycle; Pregnancy; Aging; Age factors; Lactation